2019
DOI: 10.1002/cplu.201900563
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Flower‐Like MnCo2O4@PANi‐rGO: A High‐Performance Anode Material for Lithium‐Ion Batteries

Abstract: Flower‐like MnCo2O4 was prepared in a self‐assembly process and used in the formation of MnCo2O4@polyaniline (MnCo2O4@PANi) that proceeds by a simple in situ polymerization. The MnCo2O4@PANi‐reduced graphite oxide (MnCo2O4@PANi‐rGO) composite was then synthesized by introducing rGO into MnCo2O4@PANi. This modification improves the overall electronic conductivity of the MnCo2O4@PANi‐rGO because of the dual conductive functions of rGO and PANi; it also provides a buffer for the changes in electrode volume during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Fan et al 142 reported the synthesis of MnCo 2 O 4 /rGO composites with an initial discharge capacity of 1657 mA h g −1 at a current density of 0.1 A g −1 , and a reversible capacity of 791 mA h g −1 at 0.2 A g −1 for 100 cycles. A MnCo 2 O 4 @PANi-rGO composite was also synthesized by Huang et al , 143 with a discharge capacity of 745 mA h g −1 and a coulombic efficiency of 100% after 1050 cycles at a current density of 500 mA g −1 .…”
Section: Mnco2o4-based Materials For Energy Storage Applicationsmentioning
confidence: 99%
“…Fan et al 142 reported the synthesis of MnCo 2 O 4 /rGO composites with an initial discharge capacity of 1657 mA h g −1 at a current density of 0.1 A g −1 , and a reversible capacity of 791 mA h g −1 at 0.2 A g −1 for 100 cycles. A MnCo 2 O 4 @PANi-rGO composite was also synthesized by Huang et al , 143 with a discharge capacity of 745 mA h g −1 and a coulombic efficiency of 100% after 1050 cycles at a current density of 500 mA g −1 .…”
Section: Mnco2o4-based Materials For Energy Storage Applicationsmentioning
confidence: 99%